Evaluasi Kinerja Pengelolaan Persediaan Finished Goods dengan Metode SCOR DS - Frea Marva Zerlinda; Fattah Jati Pangestu; Agung Prayudha Hidayat; Sesar Husen Santosa (AI dan SPK : Jurnal Artificial Intelligent dan Sistem Penunjang Keputusan, 2026)
Finished goods warehouse management plays a crucial role in ensuring the smooth distribution process within manufacturing companies. This study aims to evaluate inventory management performance to address the phenomenon of overcapacity resulting from inventory buildup. The evaluation was conducted using the Supply Chain Operations Reference Digital Standard (SCOR DS) framework. Through a breakdown analysis, it was found that the strategic metric Cash-to-Cash Cycle Time had the lowest performance, caused by the critical value of the operational metric Inventory Days of Supply, which was 0.03978. This finding proves that the length of time goods remain in the warehouse due to the absence of a standardized inventory movement classification system is the main cause of overcapacity. The research recommendations focus on synchronizing capacity planning to reduce storage duration and optimize warehouse space utilization.